RANCANG BANGUN SISTEM INFORMASI PENJUALAN KUE KERING BERBASIS WEB PADA TOKO AZMYA CIPETE SELATAN - Widiarti Lestariningsih; Adam Firman Firdaus (JURNAL LENTERA ICT, 2024)
Sales are a very common thing in this world, where there are two actors involved in the activity, namely the seller and the buyer. The seller acts to sell the product and receives money from the buyer, while the buyer gives money to the seller and can get the product sold by the buyer according to the agreement that is taking place. In today's advanced world, buyers do not need to purchase goods by going directly to the place of sale. By simply using a system on a device such as a smartphone, buyers can purchase goods more easily, quickly, and efficiently. Therefore, an online cake sales system was developed to make it easier for users. In this system, there are three actors: the owner, the admin, and the customer. The owner can only manage reports, while the admin can manage more than that, such as user data, product data, and others. Customers can make purchases in the system. Ultimately, this final project report examines the design and development of a web-based dry cake sales information system at the Azmya Cipete Selatan store in Jakarta.